Percepção ambiental de frequentadores de cinco praças públicas da cidade de São Paulo em relação ao seu uso e função - Oliveira, Kelly Chaves de (2015)
This paper aims to identify the relationship goers have with public squares in the city of São Paulo, SP, understanding their perceptions of the functions of these public spaces, the use done and their participation and expectations. The squares selected for this study were: Franklin Roosevelt Square, Silvio Romero Square, New World Square, Praça Benedito Calixto and Praça Floriano Peixoto. To collect data this paper is divided into two stages: first were made a qualitative and quantitative assessment of the squares through the application of the methodology of evaluation and qualification squares developed by De Angelis et al. (2004). Secondly interviews were conducted with three regulars goers of each square to check their perception of the use and function of the space and its relation to the green area. Results showed that the square should have de funcion of green aérea na local for laisure and sociaization. The square is a place chosen for the practice of everyday leisure activities to be located near the residence of its regulars. The surrounding area is also seen as part of the square, which can influence the way management of this area is done. The qualitative and quantitative evaluation of the squares shows that there is no default in the planning of structures and equipment in different places, which can be justified because they belong to different boroughs which leads to differences in the planning of these public spaces. Perceptions of the regulars can help create bases projects with similar elements that meet the expectations in common, but are flexible on some points so they can be tailored to specific needs of certain neighborhoods and types of squares.